Technological innovation in banking services: an exploratory analysis to perceptions of the front office employee - Reis, J. (2015)
It is widely recognized that the increased intensity of competition in the banking sector has had direct implications for financial institutions' approach to customers and how they define their business strategy. Considering that the current economic stance embraces innovation and technology as fundamental elements of strategic management and business and economic development, new approaches to the relationship between technological innovation and financial services are essential in achieving competitive advantage. Based on this premise, the purpose of this paper is to analyze the main effects of technological innovation on financial services at the bank branch level by evaluating responses from front office employees. The results show that information and communication technologies are an important lever in the modernization of the sector. Practical implications, strengths and limitations of our empirical study are also presented